2017
DOI: 10.1039/c7tc00598a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of formamidinium lead halide perovskite nanocrystals through solid–liquid–solid cation exchange

Abstract: Hybrid organic–inorganic formamidinium lead halide perovskite nanocrystals can be synthesized through a solid–liquid–solid cation exchange reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
106
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(116 citation statements)
references
References 43 publications
10
106
0
Order By: Relevance
“…As depicted in Figure b, the transmissions which arise from the N–H stretch (around 3400 and 3250 cm −1 ) and C–N stretch (around 1000 and 900 cm −1 ) signify the presence of in FA + /MA + in both pure EA and EA + 30% Hex treated samples . Another pronounced peak detected around 1700 cm −1 in pure EA and EA + 30% Hex treated samples represents the symmetric CN stretch that arises from the FA + in the perovskite . These ATR‐FTIR spectra imply the formation of a perovskite phase in the films with the use of pure EA and EA–Hex antisolvents.…”
Section: Resultsmentioning
confidence: 82%
“…As depicted in Figure b, the transmissions which arise from the N–H stretch (around 3400 and 3250 cm −1 ) and C–N stretch (around 1000 and 900 cm −1 ) signify the presence of in FA + /MA + in both pure EA and EA + 30% Hex treated samples . Another pronounced peak detected around 1700 cm −1 in pure EA and EA + 30% Hex treated samples represents the symmetric CN stretch that arises from the FA + in the perovskite . These ATR‐FTIR spectra imply the formation of a perovskite phase in the films with the use of pure EA and EA–Hex antisolvents.…”
Section: Resultsmentioning
confidence: 82%
“…The CN stretch (1712 cm −1 ) indicated the existence of FA + in the intermediate phase, confirming the formation of MAI-PbI 2 -DMSO+FAI-PbI 2 -DMSO. [15,27] Adv. Sci.…”
Section: Figure 1amentioning
confidence: 99%
“…The peaks at 1712 and 600 cm −1 (NH 2 ) in the Fourier transform infrared (FTIR) spectra in Figure S6 in the Supporting Information indicated the presence of FA. [27,29] In addition, the CH 3 -NH 3 + rock (991 cm −1 ) and stretch (943 and 961 cm −1 ) demonstrated the formation of α-MAPbI 3 . [30] Therefore, it can be concluded that the templateassisted perovskite structure is MAPbI 3 -FAI-PbI 2 -DMSO.…”
Section: Figure 1amentioning
confidence: 99%
“…Besides studying crystallization dynamics, tracking of ion exchange processes is possible with UV-Vis measurements. The cation exchange for the (FA,MA)PbI 3 system was shown for nanocrystals by Hills-Kimball et al [130] and for thin films by Eperon et al [95] Additionally, the suppression of anion exchange in between nanocrystals by oleate capping was studied with in situ UV-Vis by Ravi et al [29] Although not a real in situ measurement technique, it should be mentioned that the reflection spectrum from a solution during spin coating or blade coating can be used to determine the film thickness and thus to fine tune the process. Due to thin film interference the reflection profile of those films exhibit plenty of interference peaks, which with knowledge of the refractive index of the film can be used to calculate the film thickness.…”
Section: Monitoring Of Synthesismentioning
confidence: 85%